A Complex of Modules and Its Applications to Local Cohomology and Extension Functors - Bahmanpour, Kamal (Mathematica Scandinavica, 2015)
Let $(R,m)$ be a commutative Noetherian complete local ring and let $M$ be a non-zero Cohen-Macaulay $R$-module of dimension $n$. It is shown that, • if $\operatorname{projdim}_R(M)